2x-6=3x+10

Simple and best practice solution for 2x-6=3x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-6=3x+10 equation:


Simplifying
2x + -6 = 3x + 10

Reorder the terms:
-6 + 2x = 3x + 10

Reorder the terms:
-6 + 2x = 10 + 3x

Solving
-6 + 2x = 10 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-6 + 2x + -3x = 10 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-6 + -1x = 10 + 3x + -3x

Combine like terms: 3x + -3x = 0
-6 + -1x = 10 + 0
-6 + -1x = 10

Add '6' to each side of the equation.
-6 + 6 + -1x = 10 + 6

Combine like terms: -6 + 6 = 0
0 + -1x = 10 + 6
-1x = 10 + 6

Combine like terms: 10 + 6 = 16
-1x = 16

Divide each side by '-1'.
x = -16

Simplifying
x = -16

See similar equations:

| 2r-(5-r)=13+r | | 79=2x-3(4x+7) | | 10x+1=9x-11 | | 8+45r-18r^2=0 | | 51(h+1)=68h | | 25=-35-c | | 2(x-4)+2x=-6x-2 | | 9y=81-17 | | .4w+.8w-4=1 | | 6[3m-2]=24 | | 3d+3=6 | | 7|n|=56 | | 9y=17 | | -4-6(7n+2)=-6(7+2n)-4n | | 161=2(45+b) | | 6[2-4(y-1)]=6(2y+7) | | 25=-35-6 | | 23=5-2m/3 | | 2x=x-32 | | 13n=0 | | -3(2x+1)/4=3(x+4)+3/4 | | 36a^2-49y^2=0 | | 2s+13s=75 | | 2[x+2]+4=16 | | 2500=2000x-800 | | 18=6f-2(f+3) | | 5x-7=11-2x | | 8=8x-5 | | 7.5x=15.0 | | 8[k+20]=52 | | 3y+3x=15 | | .4x+1.18=3.1(2-.01x) |

Equations solver categories